Implementation of Picture Word Card Media to Improve Reading Skills of Class I Students of MIS Ar-Rahman Sindangkasih - Opin Rahma Sesar; Nurdin (Lambaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2024)
The type of research used in this research is classroom action research with the aim of finding out the implementation of picture word card media on the reading ability of class I students and to find out whether picture word card media can improve the reading ability of class I students. The subjects in this research were students of MIS Ar-Rahman Sindangkasih class IA with research procedures carried out in two cycles consisting of four stages including planning, implementation, observation, evaluation and reflection. Data collection techniques use observation, testing and documentation techniques which are analyzed descriptively. The results of the research show that 1) The process of implementing Indonesian language learning by applying picture word card learning media can be carried out in accordance with the planning and implementation stages that have been prepared which refer to the steps for implementing picture word card media. The results of teacher activity in cycle I at the first meeting were 38.8% then increased at the second meeting to 88.8%. Meanwhile, student activity in the first cycle of the first meeting was 28.58%, then increased to 85.72%. 2) Picture word card media can improve students' reading skills at MIS Ar-Rahman Sindangkasih. This can be seen in the test results obtained by students in cycle I being 50% and student learning outcomes in cycle II increasing to 79.16%. The increase in learning outcomes from cycle I to cycle II was 32.90% and the percentage increase from pre-cycle to cycle II was 66.7%.